Pemetaan Model Pengembangan Ekowisata Rejoso Mangrove Conservation dengan Metode Business Model Canvas - khafizh rosyidi (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The development of ecotourism based on coastal and marine potential is an appropriate alternative development pattern. Ecologically and economically the coastal and marine areas are very potential to be developed for the prosperity of the community. Mangrove forest is one of the potentials in the coastal area of Rejoso District, Pasuruan Regency with an area of 400,275.40 m2 located in two villages, namely Patuguran Village and Jarangan Village. Rejoso Mangrove Conservation (RMC) as a local resource which is a potential new tourist destination located at the mouth of the Rejoso coastal river. Business Model Canvas (BMC) is one of the relevant methods for answering the needs in creating a RMC ecotourism model design. The results showed that RMC Ecotourism was a diversified type. The main value offered by RMC Ecotourism is fishing tourism services and mangrove forest conservation education. BMC can make it easier for managers to see business integrity more concisely. In addition, the canvas model can also be a reliable media for compiling a series of changes and strategies for running the business.